Pengaruh Pemanfaatan Media Pembelajaran Digital Terhadap Motivasi Belajar Bahasa Arab Siswa MTs Negeri 2 Kota Bima - Rosdiana Djahibakal (Fakultas Teknik Universitas Negeri Makassar, 2026)
The rapid development of digital technology has driven significant changes in the learning process across various levels of education, including Arabic language learning in madrasahs. The utilization of digital learning media is viewed as a strategic approach to enhance students' learning motivation through the delivery of more interactive, engaging, and accessible instructional materials. This study aims to analyze the effect of digital learning media utilization on the Arabic language learning motivation of students at MTs Negeri 2 Kota Bima. Employing a quantitative approach with an explanatory survey design, the population of this study consisted of 420 students, from which a sample of 205 students was selected using Slovin's formula and proportionate stratified random sampling techniques. Data were collected via a five-point Likert scale questionnaire that had undergone validity and reliability testing. Data analysis was performed using descriptive statistics, normality tests, linearity tests, simple linear regression, t-tests, and the coefficient of determination with the assistance of SPSS version 26. The results indicate that both the utilization of digital learning media and students' Arabic language learning motivation fall into the high category. Furthermore, the simple linear regression test demonstrates that the utilization of digital learning media has a positive and significant effect on students' Arabic learning motivation; the higher the level of digital media usage, the higher the students' motivation to learn Arabic. These findings reinforce the Technology Acceptance Model (TAM) and Self-Determination Theory (SDT), which explain that the perceived ease of use and usefulness of technology, alongside the fulfillment of students' psychological needs, can successfully boost learning motivation. This study provides theoretical contributions to the development of educational technology and learning motivation research, as well as practical implications for teachers and madrasahs in optimizing the use of digital learning media.